Mechanisms for Ensuring Effective Management of Industrial Enterprises within the Framework of the Industry 4.0 Concept in TREX Encoding System - TRIFONOV, Ivan S.; KUPRIYANOV, Sergey V. (Journal of Advanced Research in Law and Economics; Vol 10 No 8 (2019): JARLE Volume X Issue 8(46) Winter 2019, 2019)
The development of the economy of the Russian Federation today is determined by the multiplicity, complexity of management and production tasks. The reforms carried out in the country's economy require serious changes in the management system in business activities. The current situation, characterized by the intensification of the processes of globalization and universal integration, dictates increased requirements for the development of domestic industry in General and its individual sectors in particular. An important condition for the sustainable development of industrial enterprises is attention to the issues of management efficiency, which implies a change in management methods and necessitates the revision and updating of management tools for the development of industrial enterprises, adequate to the market situation and allowing to take into account the diversity of challenges faced by industry enterprises. These methods and tools can be considered as a basis for ensuring the effective management of industrial enterprises, which are essentially the engines of the development of industry organizations. The TREX encoding system is designed for compact representation of the symmetric ternary number system when used in computer systems.